Problems relating to price variations faced by both bookdealers and consumers - Morad, Murizah; Ku Hamzah, Ku Nadriyah; Hassan, Faezah; Abdul Ghani, Nawadzir; Abdul Karim, Siti Sozana (1980)
Our intent has been to provide a brief introduction of those aspects of research and the subsequent compilation of data/findings; analysis and recommendations which can cover adequately in a one-semester course of study thus, this research, the product of field-work, discussions and the classroom/lectures presents the whole package of the stated problems to the solutions. We also collected and explained as clearly as possible a number of information for example; the review of literature which is related to our paper, articles from the organizations concerned (secondary data) and selected bibliographies. Illustrative materials, for the most part are drawn to supplement the analysis. The five chapters are arranged in the order in which the stages of a research project. Thus Chapter 1 gives the purpose and objective of the study, statement of problems, causes, hypotheses; Chapter 2 described the methodology used and the problems encountered during the research. Chapter 3 consists of the review of literature; Chapter 4 is the findings and analysis of primary and secondary data. Chapter 5 gives the suggested alternatives to the problems and recommendations. An appendix has been added which may be used as supplemental aids and review, also included in it are our questionnaire designs, list of bookshops and names of persons and organizations.